Implementasi Pendidikan Islam Berbasis Keberagaman (Multikultural) dalam Membina Warga Sekolah - Suparno, Suparno; Pitriani, Dian; Thoyib, Hadi; Lakoni, Lakoni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this research is to enhance students' competencies in applied research, data collection, and analysis, and to develop recommendations that benefit the school. The research method employed was qualitative, utilizing data collection techniques that included observation, interviews, and documentation. The data obtained were then analyzed using Miles and Huberman's data analysis techniques, which included data reduction, data presentation, and conclusion. The results of the study indicate: (1) a lack of respect for differences and empathy. (2) a lack of acceptance of the diversity of peers. (3) a lack of teacher training and a lack of diversity-based (multicultural) teaching materials. In conclusion, this research-based PPL can make significant contributions to institutions in developing their businesses, as well as to students in honing their analytical, problem-solving, and applied research skills. Keywords: Research-Based Internship, Experiential Learning, Learning Implementation